Intellectual Capital, Corporate Governance, and Financial Performance: The Role of Company Life Cycle - Laila Dzirwatun Nisa; Sri Hastuti (Jurnal Economia, 2026)
This research aims to investigate the impact of intellectual capital, board of directors, independent commissioners, and audit committee meetings on financial performance, with the company life cycle as a moderator. The company life cycle comprises the birth, growth, mature, shake-out, and decline stages. This research uses data from non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for the period from 2019 to 2022. In total, there are 300 observations. The data were then analyzed utilizing SPSS 23. The results of this research indicate that the board of directors and independent commissioners positively affect financial performance. Intellectual capital and audit committee meetings have no effect on financial performance. The company life cycle can moderate the influence of the board of directors and independent commissioners on financial performance. Meanwhile, the company life cycle cannot moderate the influence of the intellectual capital and audit committee meetings on financial performance.